PERILAKU DISKRIMINATIF DALAM PENGUPAHAN KERJA BAGI PEKERJA ATAU BURUH ANTARGENDER - Dewa Gede Agung (Lembaga Pengembangan Kinerja Dosen, 2022)
Discriminatory behaviour on employment for workers is due to variations in salary factors, promotion, educational background and recruitment. Low education causes mastery of science and technology to be low, so that work productivity becomes low as well. The low productivity of the workforce will affect the wages that employees or workers will receive. This research is done because there is still frequent intergender discrimination about the wage of workers or laborers, where this problem is immediately researched to obtain results or data on discrimination on wage employment. The research method used is exploratory research. The importance of the Community's role in understanding and overcoming the behavior of discrimination relating to the labor of employment between men and women. So that people can understand by not comparing gender, especially to women who work or become laborers.